(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2022)
Wireless-powered communication (WPC) is a promising technology to extend the network lifetime for varied important applications like those used hugely in commercial, industrial, transportation, and agriculture sectors. It employs a large number of low-power wireless devices in which the harvested energy from electromagnetic radiations is used for signal processing and transmission instead of the conventional wired-powered sources. Besides, non-orthogonal multiple access (NOMA) has been adopted as a vital approach to fulfill the main objectives of 5G systems and beyond. Significant research activities and advancements have taken place in this direction to support massive connectivity with higher spectral and energy efficiencies over-constrained system resources. In light of the recent developments and key challenges raised by the integrated NOMA-aided WPC networks, this study offers a thorough overview of the existing and suggested state-of-the-art technologies with their features, applications, and practical considerations. Furthermore, some of the key future research trends on this interesting topic are highlighted.